2018
DOI: 10.1111/micc.12450
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles of glucose toxicity‐exposed islet microvascular endothelial cells

Abstract: Our study provides a microcirculatory framework for gene expression profiles of glucose toxicity-exposed IMECs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Liu et al ( 161 ) determined the effects of glucotoxicity on gene expression in pancreatic islet microvascular endothelial cells (IMECs) by treating them with 5.6 mmol L-1 glucose (control group), 35 mmol L-1 glucose (glucotoxicity), and 35 mmol L-1 glucose plus 10-8 mol L-1 insulin. The study group determined that glucotoxicity resulted in the differential expression of 1,574 mRNAs compared to the control and 2,870 mRNAs relative to the insulin-treated group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al ( 161 ) determined the effects of glucotoxicity on gene expression in pancreatic islet microvascular endothelial cells (IMECs) by treating them with 5.6 mmol L-1 glucose (control group), 35 mmol L-1 glucose (glucotoxicity), and 35 mmol L-1 glucose plus 10-8 mol L-1 insulin. The study group determined that glucotoxicity resulted in the differential expression of 1,574 mRNAs compared to the control and 2,870 mRNAs relative to the insulin-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…The study group determined that glucotoxicity resulted in the differential expression of 1,574 mRNAs compared to the control and 2,870 mRNAs relative to the insulin-treated group. In addition, they also identified that these deregulated genes played roles in the regulation of proliferation, apoptosis, adhesion, migration, and metabolic activities ( 161 ).…”
Section: Discussionmentioning
confidence: 99%
“…Glucose-mediated modulation of histone methylation has also been linked to TGF-β-dependent promoters and expression of ECM-associated genes [ 13 ]. mRNA profiling by microarray analyses of mesangial and other cell types treated with elevated glucose conditions has shown changes in expected pathways like cell proliferation and metabolism, but also in pathways related to the cytoskeleton and focal adhesions [ 14 , 15 ]. The effects of glucose levels even extend to changes in alternative splicing of certain transcripts, including growth factors, their receptors, and FN [ [16] , [17] , [18] , [19] ].…”
Section: Introductionmentioning
confidence: 99%